Impact of targeted therapies in metastatic renal cell carcinoma on patient-reported outcomes: Methodology of clinical trials and clinical benefit. (February 2017) - Dos Santos, M.; Brachet, P.E.; Chevreau, C.; Joly, F.
Highlights: Metastatic renal cell carcinoma is an incurable cancer. Gain in progression-free survival with new drugs is around 3 months. Patient-reported outcomes are an essential endpoint with strong impact on clinical benefit. The quality of the methodology and the data analysis of patient-reported outcomes are not yet optimal. New-generation therapies should demonstrate not only a gain in survival but also in quality of life. Abstract: Background: Molecular targeted therapies have improved progression-free survival (PFS) without translating systematically into overall survival (OS) for patients with metastatic renal cell carcinoma (mRCC). In this population, patient-reported outcomes (PROs) have become a significant outcome. We evaluated the methodological quality of the assessment of PROs in randomized controlled trials (RCTs) and the clinical benefit of the different treatments including survival and quality of life (QoL). Methods: A systematic review identified RCTs published between January 2005 and July 2014. They were evaluated according to 11 items derived from the 2013 CONSORT PROs reporting guidelines. Survival outcomes and PROs main results were analyzed and the magnitude of clinical benefit was assessed with the European Society for Medical Oncology Magnitude of Clinical Benefit Scale (ESMO-MCBS). Results: 12 RCTs were included with a total of 22 publications. The mean CONSORT score for all items was 4.5 on an 11-point scale. No publication reported the power of the PROs analysis and only one reported a PRO hypothesis. 50% of studies did not interpret PROs in relation to clinical outcomes and only 18% discussed specific limitations of PROs and their implications for generalizability. By adding the QoL criterion to PFS, 4 trials (36.4%) obtained a high level of proven clinical benefit according to the ESMO-MCBS. Conclusion: The methodology for assessing PROs in mRCC is not optimal. Efforts should focus on defining PROs endpoint and increasing the quality of reporting of QoL. New-generation therapies in mRCC should demonstrate a gain not only in survival but also in QoL to be included in the therapeutic arsenal.